The Role of Islamic Law in Enriching the Decisions of the Indonesian Constitutional Court - Aditya, Zaka Firma; Fuadi, Abdul Basid; Yulistyaputri, Rizkisyabana (Frontiers in Law, 2023)
This article discusses the role of Islamic Law in enriching legal considerations of constitutional court decisions. As one of the recognized laws in Indonesia, it turns out that Islamic Law has an essential role in the development of national law, including the Constitutional Court decision. It was proven by the existence of 20 decisions by the Constitutional Court on judicial review of laws with Islamic Law. However, of the 20 decisions, there were only six decisions in which the Constitutional Court used Islamic Law as the basis for its consideration. In this article, we will discuss several things, namely the construction of Islamic Law and the development of positive law in Indonesia. Meanwhile, the penultimate part argues that efforts to legal positivism in Indonesia have been going on for a long time. Before conclusion, the last part believes that in fact, there are nuances of Islamic theory or Islamic Law used by the Constitutional Court judges in several decisions of the Constitutional Court.